Analysis of Immersive Virtual Reality Tourism Resources Combined with Fuzzy Comprehensive Evaluation Algorithm - Liu, Xiaoying; Li, Yingzi (Informatica, 2024)
Nowadays, transforming tourism resources into attractive tourism landscapes is a very important core task. The first problem to be solved is to conduct scientific and reasonable analysis and evaluation of tourism resources.The comprehensive evaluation of tourism resources is a prerequisite for effective protection of tourism resources, sound government and planning, and it also provides a direct theoretical basis for the planning and development of tourism resources.The existing overall evaluation methods mainly include analytic hierarchy process, principal component analysis, data report analysis, fuzzy overall evaluation, artificial neural network and evaluation methods based on the overall application of multiple methods.Among them, comprehensive fuzzy evaluation methods and neural networks have recently been widely used. This paper introduces parallel algorithms and proposes a fuzzy overall evaluation model based on parallel genetic neural network.